Spirometric alterations in adolescents AT an industrial city - Ramirez, Augusto (2001)
OBJECTIVE: To perform spirometry to a 12-to-17-year-old adolescent population living at Ciudad Nueva, Ilo, a city located near to a copper smelter-refinery and industrial fisheries with environmental pollution problems. MATERIAL AND METHODS: Spirometry was performed in 84 adolescents –34 women and 50 men– with a computerized spirometer. RESULTS: The most frequent spirometric alteration was obstruction (38,1%); restriction was found in 4,8%. The Knudson’s standards FVC, FEV1, PEF and FEF25-75% were significantly related to height, but not to age. There was statistically significant difference between genders, in favor of men, except in FEV1/FVC. FVC and FEV1 values were near to those predicted (98,8% and 93,6%, respectively), but PEF and FEF25-75% were only 80,6% and 79,6%, respectively. CONCLUSIONS: The most frequent spirometric alteration was airway obstruction. We recommend to accomplish the clinical diagnosis in these adolescents and to study other groups of inhabitants.